Chresta artemisiifolia (Vernonieae, Asteraceae), a new endangered species from a recently created protected area in the Brazilian Caatinga - Siniscalchi, Carolina M.; Loeuille, Benoit; de Siqueira Filho, José Alves; Pirani, José R. (Phytotaxa, 2019)
Chresta artemisiifolia, a new species from northern Bahia, is described and illustrated. This species occurs on rock outcrops amidst the dry Caatinga domain, and is morphologically related with C. harleyi, C. hatschbachii, C. martii and C. subverticillata. It is endemic to a region known as Boqueirão da Onça, where a national park has recently been created. We hope that the description of this taxon contributes to the efforts in the preservation of this area.